A multifaceted evaluation of microgliosis and differential cellular dysregulation of mammalian target of rapamycin signaling in neuronopathic Gaucher disease - Zhang, Zhenting; Wang, Xiaohong; Lin, Yi; Pan, Dao (Frontiers in Molecular Neuroscience, 2022)
Neuronopathic Gaucher disease (nGD) is an inherited neurodegenerative disease caused by mutations in GBA1 gene and is associated with premature death. Neuroinflammation plays a critical role in disease pathogenesis which is characterized by microgliosis, reactive astrocytosis, and neuron loss, although molecular mechanisms leading to neuroinflammation are not well-understood. In this report, we developed a convenient tool to quantify microglia proliferation and activation independently and uncovered abnormal proliferation of microglia (∼2-fold) in an adult genetic nGD model. The nGD-associated pattern of inflammatory mediators pertinent to microglia phenotypes was determined, showing a unique signature favoring pro-inflammatory chemokines and cytokines. Moreover, highly polarized (up or down) dysregulations of mTORC1 signaling with varying lysosome dysfunctions (numbers and volume) were observed among three major cell types of nGD brain. Specifically, hyperactive mTORC1 signaling was detected in all disease-associated microglia (Iba1high) with concurrent increase in lysosome function. Conversely, the reduction of neurons presenting high mTORC1 activity was implicated (including Purkinje-like cells) which was accompanied by inconsistent changes of lysosome function in nGD mice. Undetectable levels of mTORC1 activity and low Lamp1 puncta were noticed in astrocytes of both diseased and normal mice, suggesting a minor involvement of mTORC1 pathway and lysosome function in disease-associated astrocytes. These findings highlight the differences and complexity of molecular mechanisms that are involved within various cell types of the brain. The quantifiable parameters established and nGD-associated pattern of neuroinflammatory mediators identified would facilitate the efficacy evaluation on microgliosis and further discovery of novel therapeutic target(s) in treating neuronopathic Gaucher disease.